Investigation Prospects of Social Mobility of Deportees and Political Prisoners - Kuprytė, Jurgita (Genocidas ir rezistencija, 1999)
The author suggests it would be worthwhile to examine the social status and mobility of deportees and political prisoners, and most important, what impact Soviet repression had on the elite and mobility of social groups in general; whether because of deportations lost social status was recovered at least in the second or third generation and further, how family habits, behavior and group consciousness, influence social mobility.